Flood Risk Assessment for the Ganges Basin in South Asia - World Bank (World Bank, Noida, India, 2017)
The chapter wise synopsis of the report is as follows: chapter one: (present chapter) provides the reader with an overview of the project, its scope, and its objectives. It also provides the reader with an understanding of key concepts related to the project. Chapter two: describes exposure data collection and management, including the following: the data sources and the methodology for exposure data management; and exposure data development for demographic data, general building stocks, essential facilities, and transportation systems and discusses their valuation. Chapter three: provides details of the Flood Hazard Assessment, including the following: provides details on data availability required for flood assessment; provides initial results of the hydraulic model, development, calibration, and validation; and flood hazard mapping for the probabilistic events of 2, 5, 10, 25, 50, and 100-years. Chapter four: provides details of the risk assessment methodology. This includes: methodology for vulnerability functions (depth-damage function) development for various exposure classes viz. buildings, infrastructure, and agriculture etc; and methodology for loss calculation for various types of exposures. Chapter five: provides details on the findings of the risk assessment task at basin-level. Chapter six: provides details on the findings of the risk assessment task at each of the 18 sub-basins of the Ganges Basin. Chapter seven: provides the conclusions and recommendations based on the findings of the risk assessment study as a part of this assignment along with the areas to improve the study. In addition to the main report, RMSI is also providing the Ganges Basin Risk Atlas, a compendium of the main risk maps at the basin and sub-basin levels.